MAHARAH KALAM DALAM BERBAHASA ARAB PERSPEKTIF FILSAFAT ILMU - Nailis sa adah; M Yunus abu Bakar (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2025)
Maharah kalam (Speech proficiency) is one type of proficiency in Arabic. Maharah kalam is the skill of conveying messages orally using Arabic as a medium, without ignoring the rules of language use so that what is conveyed is easily understood by the person you are speaking to or the recipient of the message. The philosophy of science makes an important contribution to this scholarship. In the philosophy of science there are three main pillars in defining the object of study, namely ontology, epistemology and axiology. This article discusses maharah kalam in Arabic which is studied from the perspective of the philosophy of science. This research uses a literature review method, namely what is presented in this article comes from all types of references, such as books, articles, journals, and others. Everything is presented in depth according to the specified theme. Finally, in this research it can be concluded that maharah kalam in Arabic from the perspective of the philosophy of science shows that mastery of Arabic is not just a technical skill, but also reflects a deep understanding of the reality of the language, its epistemological processes, and the values ​​contained therein. This integration of philosophical dimensions provides a solid foundation for Arabic speaking proficiency, making it not only practically useful but also academically and spiritually meaningful..